Ultrasensitive THz Sensor Based on Centrosymmetric F-Shaped Metamaterial Resonators - Anchen Ma; Renbin Zhong; Zhenhua Wu; Yiqing Wang; Long Yang; Zekun Liang; Zheng Fang; Shenggang Liu (Frontiers in Physics, 2020)
An ultra-high sensitive metamaterials absorption sensor based on centrosymmetric double F-shaped metal resonators (CDFMR) is proposed, and its application in terahertz is analyzed. The sensor achieved perfect narrow-band absorption spectrum at 5.92 THz, with a high Q factor of 49.6. The resonance frequency is sensitive to the refractive index of the surface analyte, ultra-high sensitivity of 1,800 GHz/RIU and Fom value of 15 have been achieved. In addition, with a typical biomedical analyte of n = 1.3, the thickness sensitivity is 134 GHz/μm. It has important application in THz ultrasensitive biomedical sensor and detector.